The Ideology of Incels: Misogyny and Victimhood as Justification for Political Violence - Zimmerman, Shannon (Terrorism and political violence, 2024)
A new group of socio-political actors has emerged from the depths of the internet. Thriving in the online Manosphere, the involuntary celibates, or “Incels,” are men who feel they have been victimized by feminism. Initially just another misogynist social group online, this article argues that Incels are moving beyond social commentary to become a political movement. This article demonstrates that Incels have begun to craft a particularly violent political ideology drawing on a unique form of misogyny rooted in the construction of a counternarrative to hegemonic masculinity. Using critical narrative analysis, this article assesses the discourse and narratives used by the Incels to create their unique worldview and identifies core components of their emerging political ideology to understand how this group may justify the use of political violence as part of their political movement.